High incidence of autoimmune gastritis in patients misdiagnosed with two or more failures of H. pylori eradication. Issue 3 (19th June 2018) - Furuta, T.; Baba, S.; Yamade, M.; Uotani, T.; Kagami, T.; Suzuki, T.; Tani, S.; Hamaya, Y.; Iwaizumi, M.; Osawa, S.; Sugimoto, K.
Summary: Background: Although autoimmune gastritis (AIG) is generally considered relatively rare, we frequently encounter AIG among patients at to our hospital who have experienced at least two episodes of Helicobacter pylori eradication failure. Aims: We investigated the incidence of AIG in consecutive patients who consulted our department for H. pylori eradication with reference to eradication history. Methods: A total of 404 consecutive patients who visited the H. pylori ‐specific out‐patient unit of our hospital from June 2015 to June 2017 were enrolled. Of these, 137 were treatment‐naive, 47 had failed treatment once (single failure), and 220 had failed treatment twice or more (multiple failures) by 13 C‐UBT. Gastroscopy was performed in all patients. Culture tests of gastric mucosal samples were performed for H. pylori and other bacteria positive for urease activity. Anti‐parietal cell antibody (APCA) was measured. Patients with severe atrophy in the gastric corpus and positivity for APCA were diagnosed as having AIG. Results: A total of 43 patients were diagnosed as having AIG, of whom two were treatment‐naive (1.5%, 2/137), 1 failed eradication once (2.1% 1/47), and 40 failed treatment at least twice (18.2%, 40/220). The incidence of AIG was significantly higher in the multiple failure group than in the single failure or treatment‐naive groups. Urease‐positive bacteria, such as Klebsiella pneumoniae and alpha‐streptococcus, were identified in 33 of the 35 AIG patients who underwent culture testing. Conclusion: AIG patients were often misdiagnosed as refractory to eradication therapy, probably because achlorhydria in AIG might allow urease‐positive bacteria other than H. pylori to colonise the stomach, causing positive 13 C‐UBT results.